Analisis Perdagangan Industri Halal Dunia Studi Kasus Indonesia Cina 2020-2024 - Minda Agustina; Yusrizal; Purnama Ramadani Silalahi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze the World Halal Industry Trade Case Study Indonesia China 2020-2024. The method in this study uses library research with a narrative method. Primary data sources in this study are data obtained directly from primary sources, namely books and journals on the world halal industry trade. The data collection method used by the author is descriptive. The results of Indonesia's export trade to China in 2020 to 2024 show a positive trend of recovery and growth. China remains one of Indonesia's main trading partners, with an increase in various product sectors. Product diversification strategies and increasing added value are key to strengthening Indonesia's position in the Chinese market in the future.